CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE PADA PERUSAHAAN TERDAFTAR DI INDEKS SRI-KEHATI - STELLA STELLA; EMIR KHARISMAR; DEBBY IRWAN PUTRI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
The research objective was to analyze the effect of profitability, leverage, company age, company size, and board size on corporate social responsibility disclosure in companies listed on the SRI-KEHATI index. Population data from this study are companies registered in the SRI-KEHATI index. Using a purposive sampling method, it was found that 12 companies were consistently listed in the SRI-KEHATI index for the 2010-2018 period. This study uses multiple linear regression analysis and the panel data approach is tested through Eviews 10 with a fixed effect model to test the hypothesis. The results of this study indicate that profitability, leverage, and board size do not affect corporate social responsibility disclosure, while company age and company size have an effect on corporate social responsibility disclosure.